Vietnam : Managing Public Expenditure for Poverty Reduction and Growth, Public Expenditure Review and Integrated Fiduciary Assessment, Volume 1, Cross Sectoral Issues - World Bank (Washington, DC, 2012)
This Public Expenditure Review and Integrated Fiduciary Assessment (PER-FA) reviews and assesses the contribution that public expenditure has made to poverty reduction, and growth in Vietnam in recent years, and, identifies priorities and actions for strengthening that contribution over the coming years, through better resource allocation, and better public expenditure management. Fiscal trends have been positive, both in terms of revenue collection and expenditure outturns, resulting in a sustainable fiscal balance. Nevertheless, a number of threats to fiscal sustainability exist, and require attention over the coming years. The Government should restrict further off-budget bond issuance, channeling all Government borrowing through the budget. It should take urgent action to resolve the current expenditure arrears, largely associated with public investment in the transport and agriculture sectors-and prevent their further build up. It should strengthen arrangements for the monitoring, and management of fiscal risk, initially with better recording of domestic debt and credit, through the Development Assistance Fund (DAF). It should rapidly implement the plan to prepare a realistic and sustainable Medium-Term Fiscal Framework (MTFF) as part of every budget cycle. On reviewing the composition of public expenditure, the report states that the shares in total capital spending and total aggregate expenditure of Education and Training, and of Science and Technology, have increased significantly over the review period. Successful efforts have been made to make the transfer of resources between provinces more pro-poor, resulting in an inter-provincial transfer and revenue sharing formula, which indeed benefits poorer provinces. However, non-wage operations and maintenance expenditure fell to by 2002, while the share of capital expenditure (including major repairs) increased somehow. It is necessary to take urgent action to address an imminent maintenance crisis, and strike a balance between capital and recurrent spending. Moreover, regarding institutional aspects, further reforms are required. Efforts are required to strengthen joint working between the Finance and Planning functions at every level. The Ministry of Planning and Investment (MPI) and the Ministry of Finance (MOF) should collaborate actively with sector ministries, and provinces in the preparation of Medium-Term Expenditure Frameworks (MTEFs), building on the experience, and success of sectoral pilots. Additionally, the Government should further rationalize the roles and responsibilities of the audit and inspection functions, while appropriate monitoring measures should be implemented to ensure that fiscal transparency and reporting regulations are properly implemented at all levels of government, and by all spending units. Increased delegation to spending units is one of the key developments in public expenditure management in Vietnam in recent years. However, such delegation needs to be managed carefully if it is to result in better service delivery, and if it is to support, rather than jeopardize, equity and poverty reduction. Finally, public investment management is a critical part of public expenditure management; in Vietnam, it is particularly critical to the extent that State Budget-financed investment has grown rapidly, and now constitutes about 40 percent of the total State Budget. Analysis of recurrent costs should be built in to investment selection, and the MTEF approach should be used as a way of balancing and ensuring consistency between recurrent and capital costs.